Knoop hardness of enamel and shear bond strength of brackets bonded with composite resin with and without fluoride Dureza Knoop do esmalte e resistência ao cisalhamento de braquetes colados com resina composta com e sem flúor - Silvia Amélia Scudeler Vedovello; Marcelo Grigoletto; Mário Vedovello Filho; Heloísa Cristina Valdrighi; Mayury Kuramae (Dental Press Editora, 2012)
OBJECTIVE: The aim of this study was to evaluate the Knoop hardness of enamel, shear bond strength and failure pattern (adhesive, bracket/resin interface or mixed) after bonding and debonding brackets, using resin composite with fluoride (Ortho Lite Cure, Ortho Source®) and without fluoride (Orthobond, Morelli®). METHODS: Fragments (6 mm x 6 mm) of 40 bovine incisor crowns were embedded in acrylic self-polymerizing resin. The Knoop hardness measurements were performed before and after bonding metal brackets. The specimens were divided into two groups, according to composite resin: with fluoride (Ortho Lite Cure, Ortho Source®) and without fluoride (Orthobond, Morelli®). After bonding, the specimens were submitted to demineralization and remineralization cycling for 14 days. Shear bond strength testing was performed in a universal test machine (EMIC), at 5 mm/min crosshead speed. RESULTS: There was no significant difference in shear bond strength between Groups I and II. After demineralization and remineralization procedures (DE/RE), the specimens bonded with Ortho Lite Cure showed higher Knoop hardness than Orthobond. For both groups there was predominance of failure at bracket/resin interface. CONCLUSION: specimens bonded with fluoride resin composite showed higher microhardness after DE/RE cycling than those bonded with resin composite without fluoride, although no difference in shear bond strength was found. OBJETIVO: o propósito deste estudo foi avaliar a dureza Knoop do esmalte, resistência ao cisalhamento e padrão de falha (adesiva; interface braquete/resina; e mista) após a colagem e descolagem de braquetes, utilizando uma resina composta com flúor (Ortho Lite Cure, Ortho Source®) e uma sem flúor (Orthobond, Morelli®). MÉTODOS: fragmentos (6mm x 6mm) de 40 coroas de incisivos bovinos foram embutidos em resina acrílica autopolimerizável. A dureza Knoop foi avaliada antes e após a colagem dos braquetes metálicos. Os corpos de prova foram divididos em dois grupos: resina com flúor (Ortho Lite Cure, Ortho Source®) e resina sem flúor (Orthobond, Morelli®). Após a colagem, os corpos de prova foram submetidos ao ciclo de desmineralização e remineralização durante 14 dias, e submetidos ao ensaio de resistência ao cisalhamento em máquina universal de ensaios EMIC, com velocidade de 0,5mm/min. RESULTADOS: o ensaio de resistência de união mostrou que não houve diferença significativa entre os grupos. Após o processo de desmineralização e remineralização, os corpos de prova colados com a resina composta com flúor apresentaram maior dureza, comparados aos colados com resina sem flúor. Para ambos os grupos houve predominância de falhas na interface resina/braquete. CONCLUSÃO: os corpos de prova colados com a resina composta com flúor apresentaram maior microdureza após os processos de desmineralização e remineralização, comparados aos colados com resina composta sem flúor, porém sem diferença para a resistência de união ao cisalhamento.